Cellular Responses to the Efferocytosis of Apoptotic Cells - Yin, Charles; Heit, Bryan (Frontiers in Immunology, 2021)
The rapid and efficient phagocytic clearance of apoptotic cells, termed efferocytosis, is a critical mechanism in the maintenance of tissue homeostasis. Removal of apoptotic cells through efferocytosis prevents secondary necrosis and the resultant inflammation caused by the release of intracellular contents. The importance of efferocytosis in homeostasis is underscored by the large number of inflammatory and autoimmune disorders, including atherosclerosis and systemic lupus erythematosus, that are characterized by defective apoptotic cell clearance. Although mechanistically similar to the phagocytic clearance of pathogens, efferocytosis differs from phagocytosis in that it is immunologically silent and induces a tissue repair response. Efferocytes face unique challenges resulting from the internalization of apoptotic cells, including degradation of the apoptotic cell, dealing with the extra metabolic load imposed by the processing of apoptotic cell contents, and the coordination of an anti-inflammatory, pro-tissue repair response. This review will discuss recent advances in our understanding of the cellular response to apoptotic cell uptake, including trafficking of apoptotic cell cargo and antigen presentation, signaling and transcriptional events initiated by efferocytosis, the coordination of an anti-inflammatory response and tissue repair, unique cellular metabolic responses and the role of efferocytosis in host defense. A better understanding of how efferocytic cells respond to apoptotic cell uptake will be critical in unraveling the complex connections between apoptotic cell removal and inflammation resolution and maintenance of tissue homeostasis.